2014
DOI: 10.1093/mnras/stu1725
|View full text |Cite
|
Sign up to set email alerts
|

Why z > 1 radio-loud galaxies are commonly located in protoclusters

Abstract: Distant powerful radio-loud active galactic nuclei (RLAGN) tend to reside in dense environments and are commonly found in proto-clusters at z > 1.3. We examine whether this occurs because RLAGN are hosted by massive galaxies which preferentially reside in rich environments. We compare the environments of powerful RLAGN at 1.3 < z < 3.2 from the CARLA survey to a sample of radio-quiet galaxies matched in mass and redshift. We find the environments of RLAGN are significantly denser than those of radio-quiet gala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
121
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(134 citation statements)
references
References 75 publications
(113 reference statements)
12
121
1
Order By: Relevance
“…Brodwin et al (2013) predicted that this transition redshift should be a function of halo mass, with more massive halos transitioning earlier. This is consistent with the findings of Wylezalek et al (2014) of ã z 3 transition period for clusters around radio-loud active galactic nuclei (RLAGN), which are extreme objects that tend to reside in the most massive dark matter halos (e.g., Mandelbaum et al 2009;Hatch et al 2014;Orsi et al 2016).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Brodwin et al (2013) predicted that this transition redshift should be a function of halo mass, with more massive halos transitioning earlier. This is consistent with the findings of Wylezalek et al (2014) of ã z 3 transition period for clusters around radio-loud active galactic nuclei (RLAGN), which are extreme objects that tend to reside in the most massive dark matter halos (e.g., Mandelbaum et al 2009;Hatch et al 2014;Orsi et al 2016).…”
Section: Introductionsupporting
confidence: 90%
“…Various selection methods are used to find (proto) cluster candidates, e.g., the red sequence (Gladders & Yee 2000;Rykoff et al 2014;Licitra et al 2016), a midinfrared adaptation of the red sequence (Muzzin et al 2013;Webb et al 2015), photometric redshifts of infrared-selected samples (Eisenhardt et al 2008;Stanford et al 2012;Zeimann et al 2012), Spitzer/IRAC color selection (Papovich 2008;Rettura et al 2014), overdensities of sub-millimeter sources (Smail et al 2014;Planck Collaboration XXXIX 2015), X-ray emission (Rosati et al 1998;Tozzi et al 2015), and the Rettura et al (2016, in preparation), ground-based imaging to study the formation histories of CARLA clusters, reported in Cooke et al (2015Cooke et al ( , 2016, and a comparison of mass-matched samples of radio-loud and radio-quiet galaxies at > z 1.3, showing that RLAGN indeed reside in significantly denser environments (Hatch et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the observing program committee of ESO only granted us narrowband imaging of TXS 2353-003, not of NVSS J210626-314003, so that we were unable to do a narrowband search around this galaxy. We note, however, that selecting a galaxy based on its bright radio emission already leads to significant biases toward galaxies in dense environments (e.g., Best 2000;Ramos Almeida et al 2013;Hatch et al 2014), and we argue in the following that the stellar component of NVSS J210626-314003 itself shows some of the characteristic signatures of cluster central galaxies. Kauffmann & Charlot (1998) argued that the observed K-band magnitude can be used to approximate the stellar mass of all but the most rapidly growing galaxies out to redshifts z ≥ 2, with a scatter of about a factor of 2.…”
Section: Comparison Of Txs 2353-003 and Nvss J210620-214003 With Clusmentioning
confidence: 66%
“…It thus appears possible that the majority of massive galaxies experienced such a phase of moderate radio activity if these phases were sufficiently short (a few 10 7 yrs, see also Venemans et al 2007;Nesvadba et al 2008b). By studying a sample of radio-selected galaxies, we might expect to predominantly probe galaxies in dense environments (Best 2000;Hatch et al 2014). Eight of our sources are part of the CARLA survey (Wylezalek et al 2013) with Spitzer, which measures the density of galaxies with mid-infrared colors consistent with being at redshifts z ≥ 1.3 around HzRGs.…”
Section: A Generic Phase In the Evolution Of Massive High-redshift Gamentioning
confidence: 99%